Public Speaking Skills for dummies - Connolly, Alyson; Syahidah Samsudin (Hoboken, NJ: John Wiley & Sons, Inc., 2018)
Many of you face the idea of speaking in public with stark terror, right? Rejoice! This book will help you banish your fears for good. Whether you need to make a business pitch, give a presentation, address a conference, ace a job interview, or offer a rousing wedding toast, you'll discover how to identify and fix the problems that are stealing your confidence. You'll learn to put the right workds together and deliver them in a way that makes your listeners pay attention--and feel glad they did.-- Publishers description.
Laying the groundwork. Getting started wtih public speaking ; Getting your brain in the game -- Diagnosing and treating common afflictions. Overcoming performance anxiety ; Curing common vocal problems ; Conquering imposter syndrome: you are who you think you are -- Preparing your speech and training yourself. Crafting a captivating speech ; Using visual aids ; Being funny (or trying to) ; Practicing your speech ; Becoming a vocal athlete -- Fine-tuning your delivery. Prepping your mind for public speaking ; Mastering the ABCs of articulation ; Good vibrations: resonance -- Enhancing your speech. Breath, tone, and pitch ; Getting body language into the act ; Ready, set, go! -- It's show time: plying your trade. Acing the interview ; Engaging in witty repartee ; If at first you don't succeed -- The part of tens. Ten (or so) tips for stage fright ; Ten ways to improve your delivery ; Ten tips for preparing to speak.
Includes index
Learning made easy
Includes bibliographical references : pages 182
Keywords: Public speaking; Business presentations